Инфракрасный датчик присутствия объектов - Мизь, В. А.; Шиитов, Н. М. (ХНУРЕ, 2012)
The given work shows an infrared sensor which allows to detect object on a distance from the robot. Infrared Sensor works without physical contact between sensor and barrier. Functioning principle of developed infrared sensor is reflection. Infrared sensors measure how much infrared light is reflected from a nearby target. When a target (like surface of barrier) is approach to the infrared light-emitting diode and phototransistor pair, more of emitted light is reflected back into the sensor. Reading the sensor value is provided by reading the value from the ADC.
Keywords: infrared sensor; barrier